Mchod ʼos yoṅs rdzogs kyi bskaṅ bśags Rim pa bden gñis zuṅ ʼjug ces bya ba bźugs so - Ṅag-dbaṅ-kun-dgaʼ-bstan-ʼdzin, Khams-sprul III, 1680-1728 (Phun-gliṅ-gsuṅ-rab-ñams-gso-rgyun-spel-par-khaṅ, 1971)
Ritual text of the Drukpa Kargyudpa sect of Tibetan Buddhism.